On the Laws of Total Local Times for -Paths and Bridges of Symmetric Lévy Processes - Masafumi Hayashi; Kouji Yano (Abstract and Applied Analysis)
The joint law of the total local times at two levels for -paths of symmetric Lévy processes is shown to admit an explicit representation in terms of the laws of the squared Bessel processes of dimensions two and zero. The law of the total local time at a single level for bridges is also discussed.